Business continuity management : a practical guide - Hotchkiss, Stuart; British Computer Society, The Chartered Institute for IT (London : British Informatics Society Limited, 2010)
The book provides a clear and simple template-based approach on business continuity management. It covers all stages and issues from business impact analysis to organisational issues, escalation management and the practical aspects of running a BCM project.
Includes index
oif 15/05/14
Loan
Keywords: Emergency management; Business planning